Strategi Pemasaran Jagung di Desa Oelongko Kecamatan Bone Kancitala Kabupaten Muna - Siregar, Wa Ode Fifi Sofiani; Surni, Surni; Indarsyih, Yusna (Department of Agribusiness, Halu Oleo University, 2017)
This research aims to understand the strategic marketing of corn in Oelongko Village Bone Kancitala Sub-district Muna Regency. The determination of the research area is done purposively on the considerations that Oelongko is one of the corn-producing villages and in that location, there are only two corn merchants who do corn business around and outside Oelongko Village. This research from March until October 2017. Total of the respondent of corn merchants as much as two people by using the census method. The analysis used in this research is using a SWOT (Strength, Weakness, Opportunities, Threats) analysis method. The formulation of corn marketing strategy uses two matrixes namely SWOT matrix and external internal matrix. The result of this research showed that the strategy that needs to be applied to corn merchants in Oelongko Village is a growth strategy that can be done with diversification efforts. The diversification strategy that can be done merchants corn is an effort in the development of value added